The Ortelius Incident in the Hinlopen Strait—A Case Study on How Satellite-Based AIS Can Support Search and Rescue Operations in Remote Waters - Johnny Aase (Resources, 2017)
In this paper, Automatic Identification System (AIS) data collected from space is used to demonstrate how the data can support search and rescue (SAR) operations in remote waters. The data was recorded by the Norwegian polar orbiting satellite AISSat-1. This is a case study discussing the Ortelius incident in Svalbard in early June 2016. The tourist vessel flying the flag of Cyprus experienced engine failure in a remote part of the Arctic Archipelago. The passengers and crew were not harmed. There were no Norwegian Coast Guard vessels in the vicinity. The Governor of Svalbard had to deploy her vessel Polarsyssel to assist the Ortelius. The paper shows that satellite-based AIS enables SAR coordination centers to swiftly determine the identity and precise location of vessels in the vicinity of the troubled ship. This knowledge makes it easier to coordinate SAR operations.